Development of enzymatically-debranched starch products from sago And tapioca starch for use as fat replacer in foods. - Mohd Hani, Norziah (Universiti Sains Malaysia, 2005)
An enzymatic hydrolysis process was developed to produce starch fractions of certain composition consisting of amylose and amylopectin polymers. The method involves the use of a debranching enzyme whereby starch fractions consisting of linear chain lengths of different degree of polymerisation were produced.